2012
DOI: 10.1080/14786419.2011.573791
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HIV-1 and cytotoxicity of the alkaloids ofErythrina abyssinicaLam. growing in Sudan

Abstract: Erythrina abyssinica Lam. is an important medicinal plant growing in Sudan; its seeds were investigated for the first time for their alkaloidal constituents and biological activity. The in vitro cytotoxicity of the crude alkaloidal fraction (CAF) against the cell lines HeLa, Hep-G2, HEP-2, HCT116, MCF-7 and HFB4 showed promising activity, with IC₅₀ values of 13.8, 10.1, 8.16, 13.9, 11.4 and 12.2 µg mL⁻¹, respectively. Doxorubicin (positive control) showed in vitro cytotoxic activity with IC₅₀ values 3.64, 4.57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…Eventhough it is more famous for its bacteriostatic and antiplaque activities, its aglycone was also exhibit antiviral and HIV-1 inhibitor [10, 49], erycristagallin is a pterocarpane from Erythrina genus plants such as Erythrina orientalis [13, 23]. The plant species of Erythrina abyssinica was suggested to have anti-HIV activities [50]. However, no recent research seems to directly relate the plant activities with erycristagallin.…”
Section: Resultsmentioning
confidence: 99%
“…Eventhough it is more famous for its bacteriostatic and antiplaque activities, its aglycone was also exhibit antiviral and HIV-1 inhibitor [10, 49], erycristagallin is a pterocarpane from Erythrina genus plants such as Erythrina orientalis [13, 23]. The plant species of Erythrina abyssinica was suggested to have anti-HIV activities [50]. However, no recent research seems to directly relate the plant activities with erycristagallin.…”
Section: Resultsmentioning
confidence: 99%
“…Considering these problems, investigations of cultivars that storage erythrina alkaloids in high amounts are fundamental for a pre-clinical trial and recently it was describe a commercial sample that accumulates high levels of erythraline (Figure 1) [13]. In addition, previous investigation described a weak cytotoxicity for Erythrina alkaloids [14], which suggest also the necessity to confirm the cytotoxicity effects of pure compounds and justify the isolation for all assays.…”
Section: Introductionmentioning
confidence: 99%
“…Under the same conditions, the standard doxorubicin gave the IC 50 values of 3. 64, 4.57, 4.89, 3.74, 2.97 and 3.96 µg/ml respectively, for the same alkaloids (Mohammed et al, 2012). to 3 to activate caspase-3, these compounds may be significant lead compounds as potential therapeutics for the treatment of cancer as inducers of apoptosis in cancer.…”
Section: Resultsmentioning
confidence: 99%
“…LNCaP, PC-3, Du-145 human prostrate cancer lines) including over expression of caspace-3, has been reported (Liew et al, 2016;Christodoulou et al, 2014;Griffin et al, 2011). Potential anticancer extractives from Erythrina species including flavonoids (Kumar et al, 2013) and erythrinaline alkaloids (Mohammed et al, 2012) have also been reported. It was therefore hypothesized that erythrinaline alkaloids may directly activate human recombinant caspase-3.…”
Section: Introductionmentioning
confidence: 99%